Dental Caries: Epidemiological & Public Health Approach among Children of District Nowshera Khyber Pakhtunkhwa Pakistan - Mehwish Saba Waheed, Muhammad Fawad Shirazi, Muhammad Jibran Khan, Nadia Khan, Naeemullah, Muhammad Ishtiaq, Nizam Muhammad Darwesh, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dental caries is a global public health problem, and affects 60-90% of children; and has relationship with social; dietary; and behavioral factors. The main objective of this study was to assess the frequency and risk factors of dental caries among children of District Nowshera Pakistan. Methods: A descriptive cross sectional study was conducted in District Nowshera, in which a total of n=295 children were examined regarding presence of dental caries, from January to April 2022. A structured questionnaire was used to collect data regarding determinants of dental caries and its risk factors from parents. Data was analyzed by SPSS and results were presented in form of tables. Results: The results showed that 60.68% of children had dental caries. Approximately, 54.92% were male; 64.41% had age < 5 years; 42.03% were working mothers; and 53.56% were form rural setup. Moreover; 46.78% use toothbrush; 26.78% use fluoride toothpaste; 73.56% were breastfed; 20.0% were bottle fed; and 83.39% had night feeding. Furthermore; 29.49% children preferred high caloric food intake; 32.88% prefer sugars in food; and 47.80% added sugar during bottle feeding of their children. Conclusions: It was concluded that dental caries showed moderate to high frequency among children; and showed strong relationship family income, body mass index, parent’s education level; and job status of parents. Moreover, frequency of tooth-brushing, fluoride tooth-paste, and sugar preference showed association with dental caries and thus social, dietary and health promotion strategies were needed to reduce prevalence and complications of dental caries.